FAKTOR â FAKTOR YANG MEMPENGARUHI BELANJA MODAL PADA KABUPATEN / KOTA DI PROVINSI JAWA TENGAH TAHUN 2013-2015 - Wiwik Nur Hidayah, 14.05.52.0128; Maryono, Maryono (Students Journal of Accounting and Banking, 2018)
Capital expenditure has an important role because it has a long-term benefit to provide services to the public. So the central government should provide more activities or programs to the local government so that the program can prosper and advance the local government. This study aims to examine and analyze the effect of Local Generated Revenue, Profit Sharing Fund, General Allocation Fund, Specific Allocation Fund, Financing of Capital Expenditures in Regencies / Cities in Central Java Province in 2013-2015.The sample in this study covers all Regencies / cities in Central Java province during 2013-2015 as many as 105 data. The analysis tools used are normality test, classical assumption test, multiple linear regression test, and model test.The result showed that the Local Generated Revenue, Profit Sharing Fund, General Allocation Fund, Specific Allocation Fund and Financing has a significant positive impact on capital expenditure.Keywords: Local Generated Revenue, Profit Sharing Fund, General Allocation Fund, Specific Allocation Fund, Financing and Capital Expenditure